Global risk management : financial, operational, and insurance strategies - Choi, Jongmoo Jay; Powers, Michael R.; Fox School of Business and Management (Amsterdam ; London : JAI, 2002)
Risk management has become a wider-ranging and more vital concept as the events of September 11, 2001 have brought the risk of terrorism to the forefront of corporate decisions worldwide. The safety and security of people and physical assets and the risk of legal liability as a result of acts of terrorism have come to dominate capital markets as well as insurance and reinsurance markets. This volume provides a major contribution to the ever-evolving concepts of risk and its measurement and management, both in the U.S. and abroad.
Selected papers.
nmn 24/05/13
Loans
Keywords: Risk management; International finance